2015
DOI: 10.11606/issn.1679-9836.v94i3p154-161
|View full text |Cite
|
Sign up to set email alerts
|

Revisão sistemática sobre prevalência de demência entre a população brasileira

Abstract: Rev Med (São Paulo). 2015 jul.-set..;94(3):154-61. 154 Boff MS, Sekyia FS, Bottino CMC. Prevalence of dementia among brazilian population: systematic review / Revisão sistemática sobre prevalência de demência entre a população brasileira. Rev Med (São Paulo). 2015 jul.-set.;94(3):154-61. Artigo Desenvolvido na Disciplina Optativa "Abordagem Prática da Escrita Científica" sob coordenação da Revista de Medicina do DC-FMUSP. ABSTRACT:As the elderly population increases worldwide, the age-related diseases, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
0
10
0
11
Order By: Relevance
“… 4 The risk for onset is doubled every five years after 65 years of age, and, according to a systematic review from 2015, dementias in the Brazilian population feature a prevalence between 5.1 and 17.5%. 5 …”
Section: Introductionmentioning
confidence: 99%
“… 4 The risk for onset is doubled every five years after 65 years of age, and, according to a systematic review from 2015, dementias in the Brazilian population feature a prevalence between 5.1 and 17.5%. 5 …”
Section: Introductionmentioning
confidence: 99%
“…AD is a neurodegenerative disease that causes progressive deterioration of intellectual and routine skills, as well as cognitive impairment 4 . In Brazil, it is estimated that 6% of the 15 million people who are over the age of 60 suffer from AD 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the Global Dementia Observatory, about 50 million people suffer from dementia and there are almost 10 million new cases per year, six million of them in low-and middle-income countries [5]. In fact, Brazil has the second highest age-standardised prevalence of dementia [6], studies found rates varying between 5.1% [7] and 17.5% [8], being the point prevalence of dementia and of major neurocognitive disorder in 2018, 6.2% and 8.1%, respectively [9].…”
Section: Introductionmentioning
confidence: 99%